2021
DOI: 10.1021/acsomega.0c05708
|View full text |Cite|
|
Sign up to set email alerts
|

Febuxostat Prevents the Cytotoxicity of Propofol in Brain Endothelial Cells

Abstract: Background and purpose: A high risk of brain injury has been reported with the usage of general anesthetics such as propofol in infants. Experimental data indicated that oxidative stress and inflammation are involved in the neurotoxicity induced by propofol. Febuxostat is a novel anti-gout agent recently reported to exert an anti-inflammatory effect. The present study aims to investigate the protective property of febuxostat against the cytotoxicity of propofol in brain endothelial cells as well as the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…KLF6 is involved in multiple types of cellular progression, such as cell development, growth, signaling transition, proliferation, differentiation, and apoptosis, and the deficiency of KLF is closely associated with the development of malignant tumors [ 38 , 39 ]. Recently, KLF6 was reported to regulate the expression of CAMs and mediate adhesion between endothelial cells and monocytes [ 21 , 40 ]. In this study, we found that KLF6 was dramatically downregulated in histamine-treated hNECs but elevated by febuxostat, which is consistent with previous reports [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KLF6 is involved in multiple types of cellular progression, such as cell development, growth, signaling transition, proliferation, differentiation, and apoptosis, and the deficiency of KLF is closely associated with the development of malignant tumors [ 38 , 39 ]. Recently, KLF6 was reported to regulate the expression of CAMs and mediate adhesion between endothelial cells and monocytes [ 21 , 40 ]. In this study, we found that KLF6 was dramatically downregulated in histamine-treated hNECs but elevated by febuxostat, which is consistent with previous reports [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, KLF6 was reported to regulate the expression of CAMs and mediate adhesion between endothelial cells and monocytes [ 21 , 40 ]. In this study, we found that KLF6 was dramatically downregulated in histamine-treated hNECs but elevated by febuxostat, which is consistent with previous reports [ 21 ]. Further, we found that the inhibitory effects of febuxostat on the expression of CAMs and adhesion between histamine-treated hNECs and monocytes were significantly abolished by the knockdown of KLF6, which indicated that febuxostat exerted an anti-inflammatory effect by activating KLF6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, KLF6 knockout signi cantly increased, while its overexpression markedly reduced ROS levels in AML12 cells after hypoxia / reoxygenation. Recent studies have also shown that febuxostat inhibits oxidative stress and in ammatory responses by up-regulating KLF6, thereby reducing the toxicity of propofol to brain endothelial cells [32]. Sitagliptin attenuates high glucose-induced oxidative stress and in ammation and increases the permeability of renal tubular endothelial cells by elevating KLF6 expression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Febuxostat is an orally administered, nonpurine-selective xanthine oxidase inhibitor approved by the Food and Drug Administration (FDA) in 2009 for the management of hyperuricemia in patients with gout ( Hair et al, 2008 ; Kamel et al, 2017 ; Robinson and Dalbeth, 2018 ). In addition to the treatment of gout, febuxostat played roles in preventing the progression of periodontitis ( Nessa et al, 2021 ), preventing the cytotoxicity of propofol in brain endothelial cells ( Hao et al, 2021 ), attenuating testosterone-induced benign prostatic hyperplasia ( Abdel-Aziz et al, 2020 ), ameliorating methotrexate-induced lung damage ( Zaki et al, 2021 ), and mitigating concanavalin A-induced acute liver injury ( Maresh et al, 2020 ) in animal experiments. Moreover, febuxostat suppressed renal ischemia-reperfusion injury by modulating oxidative stress and promoting the resynthesis of adenine nucleotides ( Tsuda et al, 2012 ; Fujii et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%